Captivating technology: race, carceral technoscience, and liberatory imagination in everyday life - Benjamin, Ruha (Duke University Press, 2019)
Naturalizing coercion: the Tuskegee experiments and the laboratory life of the plantation / Britt Rusert -- Consumed by disease : medical archives, Latino fictions, and carceral health imaginaries / Christopher Perreira -- Billions served : prison food regimes, nutritional punishment, and gastronomical resistance / Anthony Ryan Hatch -- Shadows of war, traces of policing : the weaponization of space and the sensible in preemption / Andrea Miller -- This is not Minority Report : predictive policing and population racism / Joshua Scannell -- Racialized surveillance in the digital service economy / Winifred Poster -- Digital character in "the scored society" : FICO, social networks, and competing measurements of creditworthiness / Tamara K. Nopper -- Deception by design : digital skin, racial matter, and the new policing of child sexual exploitation / Mitali Thakor -- Employing the carceral imaginary : an ethnography of worker surveillance in the retail industry / Madison Van Oort -- Anti-racist technoscience : a generative tradition / Ron Eglash -- Techno-vernacular creativity and innovation across the African diaspora and Global South / Nettrice R. Gaskins -- Making skin visible through liberatory design / Lorna Roth -- Scratch a theory, you find a biography / a conversation with Troy Duster -- Reimagining race, resistance, and technoscience / a conversation with Dorothy Roberts.